A New Spectrophotometric Reagent for Fe(III): 2-(2, 3-Dihydroxy-4-oxocyclobut-2-enylidene) Hydrozinecarbothiamide and Its Application in Real Samples. (4th July 2012) - Saeidi, Mahboubeh; Aboutalebi, Reihaneh; Darehkordi, Ali
Abstract : A new reagent 2-(2, 3-dihydroxy-4-oxocyclobut-2-enylidene) hydrozinecarbothiamide has been synthesized and used for developing a simple spectrophotometric method for the determination of Fe(III) which is based on a 2 : 1 complex formation between Fe(III) and new reagent in aqueous solution. The method is optimized in terms of the pH value, amount of reagent required, ionic strength, and stability of the complex, sensitivity, linearity, and tolerance limits of various foreign ions. The complex is a red-brown chelate, with λ max = 465 nm at pH = 3 (ε = 1.95 × 10 3 L· mol −1 · cm −1 ). The ionic strength was kept constant at 0.02 by adding appropriate amounts of NaCl solution. The calibration curve is linear in the concentration range from 0.27–33.50 μ g· mL −1 . The effects of foreign ions on the determination of Fe(III) were investigated in order to assess the selectivity of the method. The method was applied in determination of Fe(III) in tap water, cow milk, and human serum.